Anti-caking compositions and methods of improving flow characteristics of hygroscopic tin salts
By mixing alumina and dried additives with Asian salt such as chlorine chloride, the problem of mobility caused by the hygroscopicity of Asian salt is solved, and better liquidity and stability have been achieved, which improves the feasibility of processing and storage. sex.
Patent Information
- Application Number
- CN202380045999.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-05-04
- Filing Date
- 2023-07-06
- Publication Date
- 2025-01-21
AI Technical Summary
The hygroscopicity of stannous salts such as stannous chloride leads to poor fluidity, making it difficult to maintain stability in transportation and storage, affecting processing and use.
By mixing the alumina and dry agent with granular Asian salt, the liquidity of Asian salt is improved. Alumina is used as intervals or carriers to reduce the adhesion of Asian salt, and dry aids such as calcium sulfate and magnesium sulfate can help reduce water absorption.
Significantly improves the flow and stability of stannous salts, reduces water absorption and risk of caking, and improves handleability in storage and processing.
Smart Images

Figure BDA0005178098240000051 
Figure BDA0005178098240000052 
Figure BDA0005178098240000061
Abstract
Description
[0001] This application claims the benefit of U.S. Provisional Application No. 63 / 368,067, filed on July 11, 2022, the entire contents of which are incorporated herein by reference. Technical Field
[0002] The present disclosure relates to a particulate composition comprising a particulate source of stannous chloride, alumina and a drying aid. The technology also relates to a method of improving the flow properties of particulate stannous chloride by mixing alumina and a drying aid with the particulate stannous chloride to impart improved flow properties to the stannous chloride. Background Art
[0003] Tin (II) (stannous) ions provided by stannous chloride and / or other stannous salts in oral compositions have long been valued for the variety of benefits they can provide, including antimicrobial effects, control of bad breath, control of plaque growth and metabolism, reduction of gingivitis, reduction of progression to periodontal disease, reduction of dentin hypersensitivity, and reduction of coronal and root caries and erosion.
[0004] Using stannous salts as raw materials can cause problems. For example, stannous chloride (II) in dihydrated and anhydrous forms is a hygroscopic material, so it attracts water vapor from the air by absorption and adsorption. This makes the powdered compound sticky. The particles can stick together, but can form agglomerates during transportation and storage, so the flowability during processing is difficult. Hygroscopic materials also have a tendency to become moist and soften over time when exposed to air containing a large amount of moisture. Therefore, the moisture content maintained by these hygroscopic salts is usually proportional to the humidity level.
[0005] Due to the above-mentioned processing problems, transporting, storing and handling stannous (II) ion salts has always been a problem in the art. It has been proven difficult to achieve the flow of stannous ion salts from storage boxes. The ideal flow design would be a simple storage box with sufficiently steep wall angles to promote mass flow. However, stannous chloride is easy to agglomerate, and simple mass flow designs do not work.
[0006] Because of these problems, drying aids are used. Commonly used drying aids are generally anhydrous inorganic salts that obtain water of hydration when exposed to moist air or wet solutions. For the most common drying agents such as sodium sulfate or magnesium sulfate, when they absorb water, the crystals form larger clumps. In organic laboratory techniques, organic solvents are dried by using anhydrous salts. Other drying aids include CaCl 2 , CaO, zeolite and silica gel.
[0007] Another way to deal with the problems associated with the hygroscopicity of stannous salts is to use anti-caking agents, which can improve flow, reduce compaction, and therefore reduce restricted flow during processing. Anti-caking agents work by absorbing excess moisture or by coating the particles to make them less prone to absorbing water. Other compounds are known to experience similar problems as stannous chloride, such as potassium nitrate.
[0008] Other objectives include finding a composition that is compatible with desiccants or drying aids for hygroscopic fluoride salts used in dental care preparations. These desiccants must be non-toxic, high purity, and food or pharmaceutical grade. In addition, the desiccants also need to have good drying properties and / or flowability for stannous salts. Summary of the invention
[0009] The present invention provides a composition comprising a particulate source of a stannous salt; an alumina or a combination of an alumina and a desiccant or a desiccant. The terms desiccant and drying aid are used interchangeably throughout the application. The particulate stannous salt may be selected from stannous chloride, stannous fluoride and / or stannous pyrophosphate. The alumina may be selected from spray dried alumina, rotary calcined alumina, fumed alumina, beaded alumina or a combination thereof. The desiccant may be any drying aid known in the art.
[0010] Also provided is a method of improving the flowability of a particulate stannous salt by adding alumina and a drying aid to a particulate stannous source such as stannous chloride, stannous fluoride and / or stannous pyrophosphate.
[0011] Additionally, compositions are provided that can be used in oral care formulations, such as toothpastes.
[0012] This summary is provided to introduce a series of concepts in a simplified form, which are further described in the detailed description below. This summary is not intended to identify key features or essential features of the claimed subject matter, nor is it intended to be used as an aid in determining the scope of the claimed subject matter. DETAILED DESCRIPTION
[0013] The following specific embodiments are merely exemplary in nature and are not intended to limit the invention or the application and use of the invention. Unless otherwise specified or apparent from the context, as used herein, the term "about" should be understood as being within the normal tolerance range of the art, such as within 2 standard deviations of the mean value. "About" can be understood as being within 10%, 5%, 1%, 0.5%, 0.1%, 0.05% or 0.01% of the value. "About" can alternatively be understood as implying the exact value described. Unless the context clearly indicates otherwise, all numerical values provided herein are modified by the term "about".
[0014] In some aspects of the composition of the present invention, the composition comprises a granular source of a stannous salt, aluminum oxide, and a drying aid. The stannous salt may be selected from stannous chloride, stannous fluoride, and stannous pyrophosphate. The stannous salt may be from one or more of the stannous salts, or a single salt such as stannous chloride.
[0015] Anhydrous grades can be provided in various forms: powder, flakes and pellets. Stannous chloride dihydrate is commercially available from various suppliers. Physical properties include a colorless crystalline material with a slight characteristic odor, poor flow characteristics and a relatively short shelf life. However, the disadvantage of using stannous chloride in dihydrate form or anhydrous form is the manufacturing restrictions in terms of transportation and handling. Both the dihydrate form and the different anhydrous forms are hygroscopic to a greater or lesser extent, making flowability difficult during processing and producing poor activity during the shelf life of the material. Stannous chloride is also an aggressive reducing agent for some metals. This characteristic can lead to the formation of undesirable compounds because the material clumps and is located at the dead point in the storage tank.
[0016] In some aspects of the composition, the stannous chloride can be selected from stannous chloride dihydrate, anhydrous stannous chloride, and combinations thereof.
[0017] In some aspects of the composition, the aluminum oxide can have an average particle size of about 0.4 micrometers (μm) to about 100 μm, or about 1 μm to about 90 μm, or about 2 μm to about 80 μm, or about 2 μm to about 30 μm, as measured by a laser diffraction particle size analyzer using a Horiba LA-960. An example is the VP Alu 100 / 30, which is a hydrophilic fumed alumina particle, i.e. a crystalline material of alumina and anatase having a white fluffy appearance, is a high purity powder or is available from Alpha High Purity Alumina (Alpha HPA) HPP, which is a rotary calcined high purity gamma alumina with spherical particles.
[0018] While not wishing to be bound by theory, it is believed that the fineness of the metal oxide is able to encapsulate the particles of the stannous salt. The metal oxide, i.e., alumina, acts as a spacer or support between the individual stannous particles, which keeps them separated from one another and ultimately reduces adhesion.
[0019] Because alumina has a positive charge, it neutralizes the negative charge of the polymer powder or negatively charged particles. This makes the powder electrically neutral and therefore resists agglomeration and sticking to walls, pipes and each other.
[0020] In some aspects of the composition, the alumina is mixed with the stannous salt in the range of about 0.5 wt % to 10 wt %, and can be about 0.5 wt % to 5 wt % mixed alumina.
[0021] In some aspects of the composition, the ratio of particulate stannous salt to alumina can be from about 9:1 to 199:1, and can be from about 19:1 to 199:1.
[0022] In other aspects of the composition, the ratio of drying aid to alumina can be about 10:1 to 2:1, or about 3:1 to 5:1.
[0023] In some aspects of the composition, the drying aid can be selected from calcium sulfate, magnesium sulfate, zinc stearate, and combinations thereof.
[0024] In other aspects of the composition, the composition further comprises one or more oral care agents selected from the group consisting of a fluoride ion source, a dental abrasive, a flavoring agent, a humectant, a chelating agent, and combinations thereof.
[0025] In some aspects, the present technology includes a method for improving the flowability of a particulate stannous salt. The method includes adding alumina and a drying aid to a particulate source of the stannous salt.
[0026] In some aspects of the method, a stannous salt selected from stannous chloride, stannous fluoride and / or stannous pyrophosphate is provided. The stannous salt can be stannous chloride, such as stannous chloride dihydrate, anhydrous stannous chloride, and combinations thereof.
[0027] In some aspects of the method, the alumina added to the stannous salt can be selected from spray dried alumina, rotary calcined alumina, fumed alumina, beaded alumina, or combinations thereof.
[0028] In some aspects of the method, a particulate stannous salt is provided.The alumina can have an average particle size of about 0.4 micrometers (μm) to about 100 μm, or about 1 μm to about 90 μm, or about 2 μm to about 80 μm, or about 2 μm to about 30 μm.
[0029] In some aspects of the method, the ratio of particulate stannous salt to alumina can be about 9:1 to 199:1, and can be about 19:1 to 199:1, and the ratio of drying aid to alumina can be about 10:1 to 2:1, or about 3:1 to 5:1.
[0030] In other aspects of the method, the drying aid added to the particulate stannous salt can be selected from calcium sulfate, magnesium sulfate, zinc stearate, and combinations thereof.
[0031] In other aspects of the method, one or more oral care agents can be added to the composition, such as fluoride ion sources, dental abrasives, flavoring agents, humectants, chelating agents, and combinations thereof.
[0032] In other aspects, the compositions can be used in oral care formulations, such as toothpastes.
[0033] Example
[0034] The following examples use known drying aids and stannous fluoride (SnF) in a humid atmosphere. 2 ) and stannous chloride (SnCl 2 ) and measure the water absorption. In the present study, the SnF 2 and SnCl 2 Water absorption in the presence of different desiccants or drying aids.
[0035] Example 1 - Water absorption test
[0036] Preparation of 3.5 grams (g) of stannous chloride (SnCl 2 ) and 0.15g desiccant (Ca 3 (PO 4 ) 2 or CaSO 4 ) and samples in which 0.15 g of a flow aid (fumed alumina) was added to stannous chloride and a desiccant as shown in Table 1 below. The salt mixture was dried in an oven at a temperature of 120°C for a specified time of 24 hours, then placed in a desiccator to cool to room temperature and weighed immediately. The salt mixture was then stored at 23°C at a constant humidity of 93% for 6 days or to reach equilibrium and the weight gain over time was recorded. The water absorption is expressed as the weight gain present. That is, water absorption % = [(wet weight-dry weight) / dry weight] × 100. The results can be seen in Table 1 below.
[0037] Table 1 - Water absorption
[0038]
[0039] The results show that the composition containing the flow aid can reduce the absorption of water by stannous chloride in the first 24 hours compared with the two-component system and can reduce the absorption of water by stannous chloride compared with the two-component system containing only Ca 3 (PO 4 ) 2 The composition when used as a desiccant significantly reduces water absorption.
[0040] Example 2 - Water absorption test
[0041] Water absorption in a constant humidity atmosphere was measured over a six day period as in Example 1. Stannous chloride was mixed with various drying aids and alumina as shown in Table 2 below.
[0042] Table 2 - Water absorption of granular stannous chloride
[0043]
[0044]
[0045] The results showed that compared with pure stannous chloride, the drying aid (Silicon dioxide), calcium sulfate, (Aluminum Oxide) with drying aid and The combination of (silicon dioxide) can reduce water absorption. Although the weight gain from stannous chloride is better in some cases and worse in others when alumina is combined with a drying aid, the physical properties are stable and significantly improved when stannous fluoride is blended with alumina, which keeps the blend dry.
[0046] Example 3 - Water absorption test
[0047] The same procedure as in Examples 1 and 2 above was followed, except that stannous fluoride was used instead of stannous chloride. The drying aids listed in Table 3 were mixed with stannous fluoride, and the water absorption was determined by the weight increase of the sample after six days in a constant humidity atmosphere.
[0048] Table 3 - Water absorption of granular stannous fluoride
[0049]
[0050] The results showed that flow aid and tricalcium phosphate were the only drying aids that did not have an appreciable weight gain compared to stannous fluoride alone. However, when stannous fluoride was blended with alumina (or alumina and calcium sulfate), the composition was able to maintain its fine, dry, powdery physical properties.
[0051] Example 4 - Fluidity Test
[0052] In the following test, a BEP model Copely flow tester was used according to the specifications detailed in European Pharmacopoeia 2.9.16-1. In this test, 100 g of stannous chloride was blended with 1.5% to 5.0% of a drying agent and 0.5% to 5.0% of a flow aid. The formulation was blended with 1% The stannous chloride sample of 119 was compared, which had a particle size of 6 microns (μm) to 15 microns (μm). Stannous chloride was blended with a drying aid and a flow aid in a tumble mixer for 10 minutes. Then 100 g of the blend was transferred to a funnel, the gate was removed, and the flow time was recorded with a stopwatch. The results are shown in Table 4.
[0053] Table 4 - Flow Test
[0054]
[0055] * Drying aid content is 5.0% by weight based on the total composition.
[0056] The results showed and Increased SnCl 2 liquidity, while using 2.5% blend in combination with drying aid improves SnCl 2 flow capacity.
[0057] Example 5 - Addition of Alumina
[0058] Use with CaSO 4 A sample of 100 g of stannous chloride as a salt mixed with zinc stearate was subjected to the following test. Added to the formulation and compared to the formulation without it. The flow time and physical properties of the formulation were measured. The results are shown in Table 5.
[0059] Table 5 - Flow test results
[0060]
[0061] The results show that calcium sulfate alone at a concentration of 5% does not improve flow properties, while concentrations of at least 5% On the other hand, if 2.5% of the drying aid is first mixed with SnCl 2 Mix and then gradually add Aeroperl, 2.1% Aeroperl is already sufficient to improve the flow of the powder mixture. If the tin chloride is mixed with the drying aid zinc stearate first, the mixture is already started with 1.5% Flow together.
[0062] Example 6 - Water absorption at constant humidity
[0063] In this example, the procedure in Example 1 was followed, i.e., a drying aid (as shown in Table 6) and alumina were added. The mixture was mixed with stannous chloride. The salt mixture was stored at 23°C for 6 days at a constant humidity of 93% and the weight gain over time was recorded. The results are shown in Table 6.
[0064] Table 6 - Water absorption test
[0065]
[0066] The results show that when aluminum oxide is used in combination with a drying aid, the water absorption of stannous chloride is reduced. Specifically, aluminum oxide is mixed with stannous chloride alone or with a drying aid such as CaSO 4, zinc stearate) provided favorable results.
[0067] Example 7 - Stannous ion stability test
[0068] The following tests were conducted to determine the stability of stannous ions in the solid particulate compositions of the formulations of the present invention. In this study, a raw material stability analysis was conducted comparing the stability of the solid particulate compositions with 10% silica ( 119) mixed with stannous fluoride. The soluble stannous content was measured by complexometric titration.
[0069] In a 250ml beaker, add 36g SnF 2 and 4 g of each drying aid (see Table 7), which were mixed and stored in a drying oven at 80°C for 24 hours. Thereafter, 60 g of H 2 O, disperse it, and stir the dispersion for another 12 hours. After the solution has settled, the supernatant is removed with a syringe, transferred to a titration template using a 0.25 μm prefilter, and measured potentiometrically.
[0070] When the stannous salt is stored at elevated temperatures (e.g. 80°C), it is expected that a portion of the drying aid will react with and be bound by the tin. 2 、SnF 2 or Sn 2 P 2 O 7 ) is dissolved in water, the concentration of free tin is now reduced. A portion of the tin(II) salt is also oxidized to tin(VI) in the air. This portion is not detected by titration. Finally, the tin(IV) ions are pathologically ineffective and therefore also lose their intended application.
[0071] SnF 2 Samples and 119. 200 was blended with tricalcium phosphate and free stannous ions were determined as described above. The results of the study can be seen in Tables 7a and 7b.
[0072] Table 7a - Stannous salt activation after storage at 80°C
[0073]
[0074] The results show that free stannous ions are significantly reduced when stannous salts are mixed with alumina, and particularly with tricalcium phosphate.
[0075] Table 7b - Stannous chloride activation after storage at 40°C
[0076]
[0077] Example 8 - Soluble Stannous Agents in Oral Care Formulations
[0078] This example indicates the loss of soluble stannous availability in the presence of the anti-caking composition.
[0079] In a 250 ml beaker, a solution of 36 wt% glycerol, 0.6 wt% sodium gluconate and 10 wt% of different anti-caking agents was prepared. The total weight of each sample was adjusted with water, and a mixture of sodium fluoride and stannous chloride (0.2543 wt% and 0.654 wt%, respectively) was added to each sample based on the total weight of the composition.
[0080] 50 ml of each prepared mixture was placed in a 150 ml beaker, stirred at 500 rpm for 24 hours with a magnetic stirrer, and then a 3 ml sample was taken out using a disposable syringe with a 0.45 μm syringe filter attached. The free tin of these samples was analyzed by potentiometric titration or via inductively coupled plasma. The results can be seen in Table 8a and Table 8b.
[0081] Table 8a - Free ion concentrations
[0082]
[0083] Table 8b - Free ion concentrations
[0084]
[0085] The results show that with the addition of up to 5% alumina, the free tin ion concentration was reduced by only about 10%. In contrast, 10% anti-caking agent resulted in a reduction of up to 70% in free tin ions. The drying aid calcium sulfate had little or no effect on the stannous ion activity. It should be noted that a 100-fold excess of drying aid was used for this test.
[0086] The above test identified calcium sulfate, zinc stearate, magnesium sulfate, pyrolytic aluminum hydroxide and fumed silica SnCl 2 The most effective anti-caking agent.
[0087] In addition, the above anti-caking agent and aluminum hydroxide ( The combination of A100 / 30) further improves the flow properties of stannous salts.
[0088] Finally, the study unexpectedly revealed that calcium sulfate inhibited the activity of free tin less than either silica-based drying aids or desiccants. The combination of not only improves the flow properties but also reduces the formulation cost of the stannous chloride blend and improves the processability in production.
[0089] Although at least one exemplary embodiment has been presented in the aforementioned specific embodiments of the subject matter of the present invention, it should be understood that there are a large number of variations. It should also be understood that an exemplary embodiment or multiple exemplary embodiments are only examples and are not intended to limit the scope, applicability or configuration of the subject matter of the present invention in any way. On the contrary, the aforementioned specific embodiments will provide a convenient roadmap for implementing the exemplary embodiments of the subject matter of the present invention for those skilled in the art. It should be understood that various changes may be made to the functions and arrangements of the elements described in the exemplary embodiments without departing from the scope of the subject matter of the present invention as set forth in the appended claims.
Claims
1. A composition comprising: a) a particulate source of a stannous salt; b) aluminum oxide; and c) Drying aids.
2. The composition according to claim 1, wherein the stannous salt is selected from stannous chloride, stannous fluoride and / or stannous pyrophosphate.
3. The composition according to claim 1 or 2, wherein the stannous salt is stannous chloride selected from stannous chloride dihydrate, anhydrous stannous chloride and combinations thereof.
4. The composition according to any one of claims 1 to 3, wherein the alumina is selected from spray dried alumina, rotary calcined alumina, fumed alumina, beaded alumina, or a combination thereof.
5. The composition of any one of claims 1-4, wherein the particulate source has an average particle size of about 0.4 micrometers (μm) to about 100 μm, or about 1 μm to about 90 μm, or about 2 μm to about 80 μm, or about 2 μm to about 30 μm.
6. The composition of any one of claims 1-5, wherein the ratio of particulate stannous salt to alumina can be from about 9:1 to 199:1, or from about 19:1 to 199:
1.
7. The composition of any one of claims 1-6, wherein the ratio of drying aid to alumina can be about 10:1 to 2:1, or about 3:1 to 5:
1.
8. The composition according to any one of claims 1-7, wherein the drying aid is selected from calcium sulfate, magnesium sulfate, zinc stearate, or a combination thereof.
9. The composition of any one of claims 1-8, further comprising one or more oral care agents selected from a fluoride ion source, a dental abrasive, a flavoring agent, a humectant, a chelating agent, or a combination thereof.
10. A method for improving the fluidity of a granular stannous salt, the method comprising: Alumina and a drying aid are added to a particulate source of stannous salt.
11. The method according to claim 10, wherein the stannous salt is selected from stannous chloride, stannous fluoride and / or stannous pyrophosphate.
12. The method according to any one of claims 10 or 11, wherein the stannous salt is stannous chloride selected from stannous chloride dihydrate, anhydrous stannous chloride, or a combination thereof.
13. The method of any one of claims 10-12, wherein the particulate source has an average particle size of about 0.4 micrometers (μm) to about 100 μm, or about 1 μm to about 90 μm, or about 2 μm to about 80 μm, or about 2 μm to about 30 μm.
14. An oral care composition, comprising: a) a particulate source of a stannous salt; b) aluminum oxide; and c) drying aids, The stannous salt is selected from stannous chloride, stannous fluoride and / or stannous pyrophosphate, the alumina is selected from spray-dried alumina, rotary calcined alumina, fumed alumina, beaded alumina or a combination thereof, and the drying aid is selected from calcium sulfate, magnesium sulfate, zinc stearate and a combination thereof.
15. A composition according to claim 14, wherein the oral care preparation is a toothpaste or gel, a mouthwash, a mouth spray, a bleach, a lozenge or a chewing gum.